2001
DOI: 10.1016/s1010-7940(01)00744-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-small cell lung cancer with single brain metastasis: the role of surgical treatment

Abstract: We can conclude that combined surgical therapy is, nowadays, the choice treatment for this kind of patients, even though restricted to selected cases. The knowledge of prognostic factors may optimize indications for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
0
55
0
Order By: Relevance
“…In good performance status (PS) patients with solitary BM and otherwise controlled systemic disease, surgical resection of the BM is a valuable treatment option [8][9][10]. Generally, surgical resection of BM is the preferred treatment in case of larger or symptomatic lesions or with a location in the vicinity of a vulnerable area.…”
Section: Introductionmentioning
confidence: 99%
“…In good performance status (PS) patients with solitary BM and otherwise controlled systemic disease, surgical resection of the BM is a valuable treatment option [8][9][10]. Generally, surgical resection of BM is the preferred treatment in case of larger or symptomatic lesions or with a location in the vicinity of a vulnerable area.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, despite there being no statistical significance, there was a serious propensity (p<0.1) for patients with adenocarcinoma to have improved survival compared to patients with other histological types. Bonnette and Granone reported similarly favorable results in terms of survival for adenocarcinomatous tumor pathology (12,13). In other retrospective studies, however, the prognostic value of primary tumor histology was shown not to be statistically significant (5,8,10,11,14,15,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 83%
“…3 Studies have been performed on the effect of neurosurgery for brain metastasis in the patients with neurological symptoms on diagnosis; however, their results were limited to patients with a solitary metastasis. [13][14][15][16] We performed early surgical treatment of brain metastasis (including multiple metastases) in patients with lowered performance status (i.e., KPS <70 or RPA class II or III) (Table 1). Early surgical treatment controlled the progression of brain metastasis and improved neurologic symptoms, and was followed by better performance status that enabled systemic chemotherapy (Fig.…”
Section: Neurological Function Scorementioning
confidence: 99%
“…15,16 Advances in surgical techniques have led to lower rates of morbidity and in-hospital mortality, with estimates as low as 1.8% in high-volume centers. 17 However, in the case of multiple brain metastases, surgery is usually limited to patients with a dominant, symptomatic, or life-threatening lesion and to those who require a tissue diagnosis before proceeding with therapy.…”
mentioning
confidence: 99%